2022
DOI: 10.17998/jlc.2022.09.18
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and prognosis of Korean patients with hepatocellular carcinoma with respect to etiology

Abstract: Background/Aim: The profile of patients with hepatocellular carcinoma (HCC) has changed globally; the role of etiology in predicting prognosis of HCC patients remains unclear. We aimed to analyze the characteristics and prognosis of Korean patients with HCC according to disease etiology.Methods: This retrospective observational study included patients diagnosed with HCC between 2010 and 2014 in a single center in Korea. Patients with HCC aged <19 years old, had coinfection with other viral hepatitis, had mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Although patients with CHB exhibited higher medical costs compared to the control group, the majority of these costs demonstrated a significant surge following the development of decompensated cirrhosis or HCC. 28 Given the recent surge in the use of costly antiviral medications, which often require long-term administration, there is a potential for further escalation in medication costs. However, considering the significant reduction in the incidence of HCC and complications related to cirrhosis due to the use of these drugs, it can be concluded that the active use of antiviral medications is cost-effective when considering the overall disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Although patients with CHB exhibited higher medical costs compared to the control group, the majority of these costs demonstrated a significant surge following the development of decompensated cirrhosis or HCC. 28 Given the recent surge in the use of costly antiviral medications, which often require long-term administration, there is a potential for further escalation in medication costs. However, considering the significant reduction in the incidence of HCC and complications related to cirrhosis due to the use of these drugs, it can be concluded that the active use of antiviral medications is cost-effective when considering the overall disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in the case of liver cancer, the majority causes are hepatis B (74%) and C (9%) viral related, while toxin- related cases are very rare in Korea. 23 If NDMA acted as a carcinogenesis enhancer, there could make a significantly higher risk in the prevalent liver cancer in Korea. However, this study did not find such an effect, suggesting that NDMA is more likely to function as a direct carcinogen rather than a carcinogenesis enhancing function.…”
Section: Discussionmentioning
confidence: 99%
“…[4] Globally, 15%-27% of patients awaiting LT die before transplantation. [7,8] In South Korea, only 2% of patients on the LT waitlist are expected to receive a deceased donor LT. [9,10] Because of the lack of donors, every country has allocation systems to objectively determine patients with poor prognosis without transplantation. Previously, various methods were used as an allocation system, and a representative example is the Child-Pugh score.…”
Section: Introductionmentioning
confidence: 99%
“…Globally, 15%–27% of patients awaiting LT die before transplantation 7,8 . In South Korea, only 2% of patients on the LT waitlist are expected to receive a deceased donor LT 9,10 …”
Section: Introductionmentioning
confidence: 99%